Pengaruh Kompetensi, Stres Kerja Dan Beban Kerja Terhadap Kinerja - Priyanto, Hadi (Universitas Sam Ratulangi, 2018)
Research purposes is to know the influence of the competency, job stress and workload to the employee performance. Sampling using sampling saturated all the counselors on â€˜Program Keluarga Harapanâ€ in Manado City that is amounted to 46 respondents. A technique that is used to test hypotheses is multiple linear regression analysis techniques (F-test for show simultant and t-test for show partial) The results of the study : F-test showed Competency, job stress and workload simultaneously influence significantly to the employee performance. t-test showed, 1) variable competency influence significantly to the employee performance, 2) variable job stress have negative significant on the performance employees, 3) variable workload influence significantly to the employee performance.Keywords: competency, job stress, workload, performance